The mechanisms of action of metformin on head and neck cancer in the pre-clinical setting: a scoping review - Huang, Lucy; Woods, Charmaine M.; Dharmawardana, Nuwan; Michael, Michael Z.; Ooi, Eng Hooi (Frontiers in Oncology, 2024)
This scoping review identifies the mechanistic pathways of metformin when used to treat head and neck cancer cells, in the pre-clinical setting. Understanding the underlying mechanisms will inform future experimental designs exploring metformin as a potential adjuvant for head and neck cancer. This scoping review was conducted according to the Joanna-Briggs Institute framework. A structured search identified 1288 studies, of which 52 studies fulfilled the eligibility screen. The studies are presented in themes addressing hallmarks of cancer. Most of the studies demonstrated encouraging anti-proliferative effects in vitro and reduced tumor weight and volume in animal models. However, a few studies have cautioned the use of metformin which supported cancer cell growth under certain conditions.